A revision of Harpochilus sheds light on new combinations under Justicia (Acanthaceae) - Da Costa-Lima, James Lucas; Chagas, Earl Celestino De Oliveira (Phytotaxa, 2019)
Until recently, Harpochilus (Acanthaceae) contained two morphologically distinct species, Harpochilus neesianus and H. phaeocarpus, from northeastern Brazil. During an analysis of herbarium collections, we found an undescribed species of Harpochilus from the Brazilian semiarid region. However, another group of botanists simultaneously discovered the species and described it as H. paraibanus. Harpochilus neesianus and H. paraibanus are similar due to their morphologically complex flowers specialized for bat pollination, nocturnal anthesis, and anthers with non-appendiculate thecae. Unlike H. neesianus and H. paraibanus, the floral morphology of H. phaeocarpus and Cyrtanthera citrina, a name used for several misidentified collections of H. paraibanus, is more similar to that of Justicia. Thus, these species are here combined under Justicia. We also provide additional information on the morphology, geographic distribution and conservation status of H. paraibanus, and propose lectotypes for Harpochilus, H. neesianus, and C. citrina.